Pengaruh Strategi Pemasaran dan Pemanfaatan Media Sosial terhadap Kepuasan Pelanggan dan Minat Pembeli sebagai Variabel Intervening (Studi Kasus Generasi Milenial di Marindal II) - Niat Noverlin Zai; Sukahati Giawa; Nirmadaningsih Hiya; Yulia Tiara Tanjung (Departement of Mathematics Education, 2023)
The millennial generation is a modern generation living at the turn of the millennium. Simultaneously, in this era digital technology is starting to penetrate all aspects of life. The millennial generation or what is also called generation Y was born around 1980 to 2000. This research aims to determine the influence of marketing strategies and the use of social media on customer satisfaction and buying interest as intervening variables in the millennial generation in Marindal II. This research uses quantitative methods, the sample of this research is 100 respondents, the results of this research are based on the t or partial test which states that there is no significant influence between marketing strategies on customer satisfaction. There is a significant influence between the use of social media on customer satisfaction. There is no significant influence. Between Purchase Interest and Customer Satisfaction, there is a significant influence between the Marketing Strategy variable on Purchase Interest. There is a significant influence between the Marketing Strategy variable on Customer Satisfaction which is mediated by Purchase Interest. There is no significant influence between the use of Social Media and mediated Customer Satisfaction. By Purchase Interest.